Penggunaan Lembar Kerja Siswa Berbasis Theory Of Didactical Situation Melalui Moodle - Devit Juliani (Jurnal THEOREMS (The Original Research of Mathematics), 2023)
The current technological development is capable of transforming the education system. The utilization of digital media in learning has become one of the factors influencing students' success in studying mathematics. This research aims to investigate the use of student worksheets based on the Theory of Didactical Situation in mathematics learning through Moodle. The research adopts a qualitative approach with a descriptive method. The topic studied in the student worksheets is Tangent Lines to Circles. The data collection techniques used are documentation, interviews, and observations. The subjects of this research are 30 eighth-grade students at SMPN 2 Karawang Barat. The research findings indicate that the use of student worksheets based on the Theory of Didactical Situation in mathematics learning through Moodle has been implemented successfully, received positive responses from students, and improved students' ability to understand mathematical concepts.Keywords: Didactical Situation, Moodle, Mathematics Learning